Venous thromboembolism during pregnancy, postpartum or during contraceptive use - Blanco-Molina, Ángeles; Rota, Lidia; Micco, Pierpaolo Di; Brenner, Benjamin; Trujillo-Santos, Javier; Ruiz-Gamietea, Angeles; Monreal, Manuel; the RIETE Investigators (Thrombosis and Haemostasis, 2010)
Venous thromboembolism (VTE) is a leading cause of maternal death during pregnancy or postpartum, and in women using hormonal contraceptives. However, important issues concerning its natural history and therapy remain unsolved, and most of the protocols for treatment of VTE in this patient population are based on data extrapolated from other populations. RIETE is an ongoing registry of consecutive patients with objectively confirmed, symptomatic, acute VTE. We examined the clinical characteristics and three-month outcome of all enrolled women with pregnancy, postpartum or using hormonal contraceptives. As of December 2008, 173 pregnant women, 135 postpartum, and 798 contraceptive users were enrolled. Of these, 438 (40%) presented with pulmonary embolism (PE) and 668 with deep-vein thrombosis (DVT). Most women with acute PE had dyspnea (72%) or chest pain (75%), but only 2.0% had hypoxaemia. During the three-month study period, five women (0.45%; 95% CI: 0.17–1.00) died (3 had fatal PE), 13 (1.18%; 95% CI: 0.66–1.95) had VTE recurrences, and seven (0.63%; 95% CI: 0.28–1.25) major bleeding. Two of the three women with fatal PE died during the first few hours after arriving at the emergency ward, with no time to start any therapy. The outcome of pregnant or postpartum women with VTE is similar to that in contraceptive users, even though the treatment is different. The non-specific nature of PE signs may have caused some delay in PE diagnosis.
Keywords: Pregnancy; postpartum; contraceptives; venous thromboembolism